Accessing Software: Emulation in Information Institutions. - Acker, Amelia (Information & Culture, 2024)
This article explores the challenges faced by libraries, archives, and museums in preserving and providing access to software and software-dependent information. It discusses the implementation of software emulation workflows in three information institutions and examines the technical and social constraints of emulation. The article emphasizes the importance of transparency and accountability in preservation workflows and highlights the complexities of providing access to emulated software, including the challenges of emulating unique controllers. It also discusses the concept of "automagic" access and the need for further research on intervention and visibility strategies in software preservation.